Reactividad Alcali-Silice de las Combinaciones Cementantes con Agregados Petros de las Minas Sillahuan y Salazar, Riobamba - Cargua Huaraca, Jose Andres (2023)
Guaranteeing a safe and serviceable reinforced concrete structure is the duty of every engineer when designing and building it. Concrete structures are daily subjected to different physical or chemical attacks. Depending on the type of structure. Necessary studies are performed to ensure safety in the structure. Soil studies, and structural calculations are essential for this. However, the analysis of materials is also an important aspect of the design of civil work. Since there are some internal factors of each material that can compromise the entire structure. Among the attacks that a structure can suffer, especially in concrete, we have the alkali-aggregate reaction, a chemical reaction that occurs in the internal system of the concrete between the cementitious material and the stone aggregate. In the presence of water, it produces a gel that expands, breaking the concrete from the inside. Among the alkali-aggregate reactions, we have the alkali-silica response, which is considered the most damaging. It is a reaction between the cement's alkali and the aggregate silica, causing an internal gel that expands and destroys the concrete structure from the inside, causing the system to tend to collapse. In the present investigation, tests were conducted to determine the alkali-silica reaction potential of aggregates from the SILLAHUAN and SALAZAR mines in the city of Riobamba in combination with cementitious material type IP and GU corresponding to the HOLCIM and CHIMBORAZO brands, respectively. The X-Ray Fluorescence test was conducted to determine the chemical composition of each material, both the stone and the cementitious materials. And to determine the alkali-silica potential of the aggregate-cement combinations, the Accelerated Mortar Bar Method test was performed according to ASTM C 1567. The expansions obtained by performing the test showed that the stone and cementitious materials have a high alkali-silica reactivity potential. The combinations of the Sillahuan and Salazar mines with IP type cement showed the most detrimental behavior. Likewise, the combination of the Salazar mine with GU type cement had an expansion that exceeds the limit established by the standard. On the other hand, the expansions presented by the combination of aggregates from the Sillahuan mine with GU cement were the most acceptable, below the established tolerance. Keywords: durability, reactivity, alkali-silica, aggregate, cement, expansion.